Management and entrepreneurship in societal transformation : perspectives from Africa - Adebola, S.A.; Gbadeyan, R.A.; University of Ilorin, the Department of Business Administration (Ilorin, Nigeria : University of Ilorin, the department of Business Administration, 2013)
The book is a compilation of scholarly articles in honour of Prof. Jackson O. Olujide and covers major issues in management and entrepreneurship in Africa, such as, challenges to entrepreneurship in Nigeria; the contributions of universities to management and entrepreneurship development.
Includes references.
rua 24/06/14
Loans
Keywords: Entreprenuership; Entreprenuerial managment; Societial change; Social science and management; Africa